2020
DOI: 10.1532/hsf.3093
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Isolated Tricuspid Valve Surgery

Abstract: Background: Isolated tricuspid valve surgery is a rarely performed procedure and traditionally is associated with a bad prognosis, although its clinical outcomes still are little known. The aim of this study was to assess the short- and long-term clinical outcomes obtained at our center after isolated tricuspid valve surgery as treatment for severe tricuspid regurgitation. Methods: This retrospective study included 71 consecutive patients with severe tricuspid regurgitation who underwent isolated tricuspid val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 32 publications
0
5
0
Order By: Relevance
“… 10 , 11 Other studies have reported in-hospital mortality rates within a varying range of 10 to 13%. 12 , 13 , 14 The individualized perioperative care provided by a single surgeon in our Mini-TVS experience may have contributed to the positive surgical outcomes in this cohort. Furthermore, our previous ITV national outcomes study showed no difference in in-hospital mortality between TVR and TVre.…”
Section: Discussionmentioning
confidence: 97%
“… 10 , 11 Other studies have reported in-hospital mortality rates within a varying range of 10 to 13%. 12 , 13 , 14 The individualized perioperative care provided by a single surgeon in our Mini-TVS experience may have contributed to the positive surgical outcomes in this cohort. Furthermore, our previous ITV national outcomes study showed no difference in in-hospital mortality between TVR and TVre.…”
Section: Discussionmentioning
confidence: 97%
“…However, use of this method for tricuspid valve surgery in dogs has not yet been reported. In human medicine, De Vega annuloplasty is useful for correcting functional TR with low longterm recurrence rates (16,(19)(20)(21)(22). In human patients, the target annulus diameter is decided using an index calculated according to body surface area.…”
Section: Discussionmentioning
confidence: 99%
“…The indication and therapeutic approach were discussed by the multidisciplinary heart team. Despite a moderate STS Score = 5.17% and EuroScore II = 5.24%, a conventional open surgery was ruled out, considering the poor risk-benefit ratio expected as largely reported in the literature of isolated tricuspid reoperations [6][7][8]. TTVR was the therapy of choice for her.…”
Section: Case Reportmentioning
confidence: 99%
“…Because of this, it has been relatively neglected both in the literature and clinically as compared to the primary left-sided diseases [3]. Furthermore, the rarity of TV surgical management, and its high post-operative mortality and morbidity [7][8][9], in addition to the lack of evidence proving the superiority of surgical treatment over medical therapy in severe TR [10], has led it to be called the "forgotten valve" for a long time [3,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation